The unveiling of the Beethoven monument in Vienna. - Katzler, Vincenz, 1823-1882 (artist):::Creator::::::::::::; Zumbusch, Kaspar Clemens Eduard, Ritter von, 1830-1915 (sculptor):::Contributor::::::::::::
Color illustration of the unveiling ceremony for the Beethoven monument in Vienna